PENGARUH INTEGRATED MARKETING COMMUNICATION (IMC) TERHADAP KEPUTUSAN PEMBELIAN PRODUK RAJUTAN PADA CV. EKA JAYA MANDIRI BINONG JATI BANDUNG - Perwito Perwito; Dheani Andaresta (POLITEKNIK PIKSI GANESHA, 2022)
The purpose of this study was to determine the effect of integrated marketing communication (IMC) on purchasing decisions of knitted products at CV. Eka Jaya Mandiri in January 2020, as well as to find out the problems and efforts made related to integrated marketing communication (IMC) and purchasing decisions on CV. Eka Jaya Mandiri. This study uses a quantitative descriptive method with the data source from the respondent's questionnaire. The data collection technique obtained is by means of field work practices and literature studies. Based on the results of data analysis, the effect of integrated marketing communication (IMC) on purchasing decisions has a close relationship of 0.730 strong category. Integrated Marketing Communication (IMC) affects the Purchase Decision by 53.3% and the remaining 46.7% is influenced by other variables. The problem that occurs is Integrated Marketing Communication (IMC) in CV. Eka Jaya Mandiri has not been carried out optimally, because many programs and planning concepts are not operated and are underdeveloped. However, to overcome this problem, the company makes efforts to develop programs and promotional planning concepts, while the advice given is that companies need to pay attention to sales health, maximize all promotional sources that will be run, and collaborate with other companies or institutions in the business field.